Unicystic high‐grade intraductal carcinoma of the parotid gland: cytological and histological description with clinic–pathologic review of the literature. Issue 9 (29th August 2018) - Palicelli, Andrea; Barbieri, Paola; Mariani, Narciso; Re, Paola; Galla, Stefania; Sorrentino, Raffaele; Locatelli, Francesca; Salfi, Nunzio; Valente, Guido
Abstract : Intraductal carcinoma of the salivary glands is a rare, not well‐characterized tumor. We reviewed the literature and report the first case of a high‐grade unicystic intraductal carcinoma of the parotid. Formalin‐fixed/paraffin‐embedded blocks were sectioned and stained for hematoxylin and eosin and immunostains (CAM5.2, EMA, CK5, p53, p63, SMA, S100 protein, DOG1, mammaglobin, AR, ER, PR, Her‐2, and Ki67). A 72‐year‐old man showed a painless nodule (2 cm) in the right parotid region. A 'tumor of uncertain malignant potential' (low grade) was diagnosed by fine‐needle aspiration cytology (FNAC). Preoperative magnetic resonance imaging revealed a well‐delimited, oval cyst without evidence of parenchymal invasion (T1‐scans: homogeneously isointense with hypointense thin peripheral ring; T2‐scans: strongly hyperintense). Histological examination confirmed a unilocular cyst lined by a multistratified epithelium arranged in solid, pseudopapillary, cribriform, and 'incomplete cribriform/microcystic' patterns. Tumor cells were CAM5.2+, EMA+, mammaglobin+, AR+, p63+ (focal), CK5+ (focal), p53 (+, 20%), ER‐, PR‐, S100 protein‐, DOG1‐, and Her‐2‐. A continuous peripheral layer of p63+/CK5+/SMA+ myoepithelial cells proved the ' in situ' nature of the tumor. The evidence of focal severe nuclear atypia, high mitotic index (12 mitoses/10HPFs), and high proliferation index (40%) favored a high‐grade intraductal carcinoma. Preoperative FNAC and clinic–pathologic correlation are very helpful. Discrepancy in dysplasia grade between FNAC and resected specimen can occasionally occur (especially in case of focal high‐grade features). Total sampling should exclude invasive areas or other cystic malignancies.